Cyber safe identifying and combating cyber bullies - Donato, Aaron Firth; Preston, Luke; De Robbio, Michael; Video Education Australasia (Australia : Video Education Australasia, 2007)
Looks at what cyber bullying is; cyber stalking and the law; and what students can do to protect themselves from this ever increasing threat. Education for parents and school communities is also examined, with strategies on how to deal with cyber bullying and positive school wide solutions
Executive producer, Mark McAuliffe ; camera, Nicholas Hansen
Voice over: Amanda Brocklebank
DVD format
Keywords: Internet -- Security measures; Cyberbullying; Cyberstalking